A review of the health problems of the internally displaced persons in Africa. (2016)
Globally, over 40 million people were displaced as a result of wars and violence due to religious and ethnic conflicts in 2015 while 19.2 million were displaced by natural disasters such as famine and floods. In Africa, 12 million people were displaced by armed conflict and violence and there were hundreds of thousands of people displaced by natural disasters. Despite these large numbers of internally displaced persons (IDPs) in Sub‑Saharan African countries and the potentially negative impact of displacement on the health of these populations, there is limited information on the health problems of IDPs in the region. The previous studies have mainly focused on the health problems of refugees and single disease entities among IDPs. However, a more comprehensive picture is required to inform the provision of adequate healthcare services for this vulnerable population. The objective of this review was to fill this knowledge gap. Bibliographic databases were searched and screened, and nine studies were selected and reviewed. The major physical health problems and symptoms were fever/malaria (85% in children and 48% in adults), malnutrition in children (stunting 52% and wasting 6%), malnutrition in adult males (24%), diarrhoea (62% in children and 22% in adults) and acute respiratory infections (45%). The prevalent mental health problems were post‑traumatic stress disorder (range: 42%–54%) and depression (31%–67%). Most of the studies reviewed focused on mental health problems. Limited evidence suggests that IDPs experience various health problems but more research is required to inform the provision of adequate and comprehensive healthcare services for this group of individuals